2022
DOI: 10.3892/mmr.2022.12925
|View full text |Cite
|
Sign up to set email alerts
|

An angiogenesis‑related lncRNA signature for the prognostic prediction of patients with bladder cancer and LINC02321 promotes bladder cancer progression via the VEGFA signaling pathway

Abstract: The mechanism underlying bladder cancer metastasis is associated with tumor angiogenesis. The present study aimed to evaluate the predictive role and value of an angiogenesis-associated long non-coding (lnc)rna signature in patients with bladder cancer and the role of long intergenic non-coding rna (linc)02321 in the progression of this malignancy. angiogenesis-related lncrnas were screened using Pearson correlation analysis and the signaturewas constructed using cox regression analysis and evaluated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The application of lncRNA expression-based lnc signatures in predicting NAC response or prognosis has been widely investigated in various studies. Li et al constructed an angiogenesis-associated lnc signature based on the expression of six angiogenesis-related lncRNAs to predict the prognosis of bladder cancer patients [50]. Mansy et al developed a lncRNAs signature "PVT1, TUG1, and MEG3" to predict cisplatin resistance in ovarian cancer patients [51].…”
Section: Discussionmentioning
confidence: 99%
“…The application of lncRNA expression-based lnc signatures in predicting NAC response or prognosis has been widely investigated in various studies. Li et al constructed an angiogenesis-associated lnc signature based on the expression of six angiogenesis-related lncRNAs to predict the prognosis of bladder cancer patients [50]. Mansy et al developed a lncRNAs signature "PVT1, TUG1, and MEG3" to predict cisplatin resistance in ovarian cancer patients [51].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have found that USP30-AS1 influences the activation of macrophage-like cells. Interestingly, USP30-AS1 has been implicated to be a potential prognostic risk factor for cancer and to play a role in cell death (e.g., apoptosis, autophagy, ferroptosis, and necroptosis) [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. Furthermore, USP30-AS1 promotes cell viability and inhibits apoptosis in acute myeloid leukemia cell lines, including THP-1 [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…TPRG1-AS1 inhibits the transcription of CRTAC1 by recruiting a DNA methyltransferase to the promoter of CRTAC1 and increasing the DNA methylation of its promoter. CRTAC1 inhibits glycolysis and angiogenesis in BC cells Kang et al [ 113 ] lncRNAs (USP30-AS1, LINC02321, PSMB8-AS1, KRT7-AS, LINC01767, and OCIAD1-AS1) Bioinformatics analysis BC RNA-sequencing and clinical data were downloaded from the TCGA database ( https://portal.gdc.cancer.gov/ . TCGA-BLCA) lncRNA expression data in BC from the TCGA database were assessed using scripts written using the “Perl” (version 5.32.1.1) programming language Six angiogenesis-associated lncRNA signatures reported in the study may be used to predict the prognosis of patients with BC, and LINC02321 promoted malignant progression of BC via the VEGFA signalling pathway PTEN , phosphatase and tensin homolog; FOXA1 , forkhead box A1; TFAP2A , transcription factor AP-2 alpha …”
Section: The Regulatory Role Of Tumour Microenvironment and Its Impac...mentioning
confidence: 99%